2021
DOI: 10.3390/md19100547
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Conotoxin Precursors from the Cone Snail Conus spurius by High-Throughput RNA Sequencing

Abstract: Marine gastropods of the genus Conus, comprising more than 800 species, have the characteristic of injecting worms and other prey with venom. These conopeptide toxins, highly diverse in structure and action, are highly potent and specific for their molecular targets (ion channels, receptors, and transporters of the prey’s nervous system), and thus are important research tools and source for drug discovery. Next-generation sequencing technologies are speeding up the discovery of novel conopeptides in many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…A conotoxin precursor typically comprises 6-50 amino acid residues (aa) with an N-terminal hyper-conserved signal peptide region, a precursor region that may be present or absent, and a C-terminal hyper-variable mature toxin region (Livett et al, 2004;Kaas et al, 2010;Jin et al, 2019b). Conotoxins have high diversity, with a detailed classification of more than 28 different gene superfamilies (namely A, B1, B2, B3, C, D, E, F, G, H, I1, I2, I3, J, K, L, M, N, O1, O2, O3, P, Q, R, S, T, V, Y) and 13 temporary gene superfamilies (Olivera et al, 1999;Kaas et al, 2010;Kaas et al, 2012;Puillandre et al, 2012;Ye et al, 2012;Aguilar et al, 2013;Dutertre et al, 2013;Luo et al, 2013;Li et al, 2020;Zamora-Bustillos et al, 2021). A total of 31 types of cysteine frameworks (I-V, VI/VII, VIII-XXX, XXXII, and XXXIII) and 12 pharmacological families (a, g, d, ϵ, i, k, µ, r, s, t, c, and wfamilies) have been defined by their molecular targets and pharmacological activities, respectively (Kaas et al, 2010;Kaas et al, 2012;Bernaldez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conotoxin precursor typically comprises 6-50 amino acid residues (aa) with an N-terminal hyper-conserved signal peptide region, a precursor region that may be present or absent, and a C-terminal hyper-variable mature toxin region (Livett et al, 2004;Kaas et al, 2010;Jin et al, 2019b). Conotoxins have high diversity, with a detailed classification of more than 28 different gene superfamilies (namely A, B1, B2, B3, C, D, E, F, G, H, I1, I2, I3, J, K, L, M, N, O1, O2, O3, P, Q, R, S, T, V, Y) and 13 temporary gene superfamilies (Olivera et al, 1999;Kaas et al, 2010;Kaas et al, 2012;Puillandre et al, 2012;Ye et al, 2012;Aguilar et al, 2013;Dutertre et al, 2013;Luo et al, 2013;Li et al, 2020;Zamora-Bustillos et al, 2021). A total of 31 types of cysteine frameworks (I-V, VI/VII, VIII-XXX, XXXII, and XXXIII) and 12 pharmacological families (a, g, d, ϵ, i, k, µ, r, s, t, c, and wfamilies) have been defined by their molecular targets and pharmacological activities, respectively (Kaas et al, 2010;Kaas et al, 2012;Bernaldez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality and coverage of assembled contigs must be carefully examined to avoid potential artifacts that conotoxin sequence diversity may be overestimated (Jin et al, 2019a;Dutt et al, 2019;Abalde et al, 2020;Peng et al, 2021). The NGS has been employed to determine the diversity of conotoxins in 31 Conus species, such as Conus (Textilia) bullatus (Hu et al, 2011), Conus (Pionoconus) magus (Pardos-Blas et al), C. striatus (Himaya et al, 2021), Conus (Dendroconus) betulinus (Peng et al, 2016), Conus (Kioconus) tribblei (Barghi et al, 2015) and Conus spurius (Zamora-Bustillos et al, 2021), discovering 100-400 different conotoxins per Conus species. Nevertheless, based on the public ConoServer database, only 8,360 conotoxins from 122 cone snails have been identified, representing < 2% of the total estimated conotoxins (Lu et al, 2014;Peng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all predicted I1 and I2 peptides were localised in the distal section with little or expression in the proximal section in both species ( Figure 5 A, Table S3 ). Previous studies have shown that I1 and I2 peptides can be dominant in worm-hunting cone snails ( Table S4 ) [ 18 , 27 , 30 , 31 , 32 , 33 , 34 ] and might be exclusively used for predation. On the other hand, predicted O1 peptides were found in both distal and proximal segments of the venom duct.…”
Section: Resultsmentioning
confidence: 99%
“…O1, M, and T conotoxin are widespread among cones and likely provide a minimal set of conotoxins required for the effective function of the venom [ 7 , 9 , 38 ]. Table S4 shows the venom profiles of 21 published worm-hunting cone snail transcriptomes from 12 clades widely distributed in the Indo-Pacific [ 18 , 19 , 27 , 30 , 31 , 32 , 33 , 34 ]. As noted in Table S4 , approaches used to obtain these data differ and thus any comparisons are qualitative in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation